Modeling of IP-GMPLS multimedia traffic and network for admission control using ns-2 - Din N.M.; Fisal N. (2023)
We present our work on modeling multimedia traffic over an Internet Protocol - Generalised Multiprotocol Label Switching (IP-GMPLS) network for admission control using the network simulator ns-2. GMPLS networks are potential solutions to an all optical internet environment. To generate GMPLS network scenarios the MPLS components in the ns-2 was utilized. The multimedia traffic comprised of real time voice, real time video and best effort internet traffic. The network was validated using queuing theory and the blocking probability of the network was used as the performance evaluation parameter. 2008 IEEE.